Functional characterization of bitter-taste receptors expressed in mammalian testis - Xu, Jiang; Cao, Jie; Iguchi, Naoko; Riethmacher, Dieter; Huang, Liquan (Molecular human reproduction, 2013)
Mammalian spermatogenesis and sperm maturation are susceptible to the effects of internal and external factors. However, how male germ cells interact with and respond to these elements including those potentially toxic substances is poorly understood. Here, we show that many bitter-taste receptors (T2rs), which are believed to function as gatekeepers in the oral cavity to detect and innately prevent the ingestion of poisonous bitter-tasting compounds, are expressed in mouse seminiferous tubules. Our in situ hybridization results indicate that Tas2r transcripts are expressed postmeiotically. Functional analysis showed that mouse spermatids and spermatozoa responded to both naturally occurring and synthetic bitter-tasting compounds by increasing intracellular free calcium concentrations, and individual male germ cells exhibited different ligand-activation profiles, indicating that each cell may express a unique subset of T2r receptors. These calcium responses could be suppressed by a specific bitter-tastant blocker or abolished by the knockout of the gene for the G protein subunit α-gustducin. Taken together, our data strongly suggest that male germ cells, like taste bud cells in the oral cavity and solitary chemosensory cells in the airway, utilize T2r receptors to sense chemicals in the milieu that may affect sperm behavior and fertilization.